2014
DOI: 10.1097/ta.0b013e3182aafe50
|View full text |Cite
|
Sign up to set email alerts
|

Cost-utility analysis of prehospital spine immobilization recommendations for penetrating trauma

Abstract: BACKGROUND:The American College of Surgeons' Committee on Trauma's recent prehospital trauma life support recommendations against prehospital spine immobilization (PHSI) after penetrating trauma are based on a low incidence of unstable spine injuries after penetrating injuries. However, given the chronic and costly nature of devastating spine injuries, the cost-utility of PHSI is unclear. Our hypothesis was that the cost-utility of PHSI in penetrating trauma precludes routine use of this prevention strategy. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The studies included in the review did not consistently use the recommended societal perspective for accounting for costs, use multiple resource utilization categories, use constant dollars, discount future costs and outcomes, use a lifetime horizon, or include an indication of uncertainty in results using 95% confidence or uncertainty intervals (Table 2). Garcia, Liu, & Victorino (2014) and Freedberg et al (2006) incorporated the most guideline recommendations in their studies compared to other studies included in the review.…”
Section: Resultsmentioning
confidence: 99%
“…The studies included in the review did not consistently use the recommended societal perspective for accounting for costs, use multiple resource utilization categories, use constant dollars, discount future costs and outcomes, use a lifetime horizon, or include an indication of uncertainty in results using 95% confidence or uncertainty intervals (Table 2). Garcia, Liu, & Victorino (2014) and Freedberg et al (2006) incorporated the most guideline recommendations in their studies compared to other studies included in the review.…”
Section: Resultsmentioning
confidence: 99%
“…13 Prehospital spine immobilization is not cost-effective for penetrating torso or extremity injuries and is unlikely to be advantageous for penetrating head injuries. 5 Cervical spine immobilization has the potential to mask potentially life-threatening conditions and impede airway or hemorrhage management. Specifically, cervical spine immobilization has been associated with an increased number of intubation attempts.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on spinal motion restriction (SMR) in penetrating trauma have indicated a lack of cost-effectiveness as well as an increased risk of mortality. [4][5][6] The use of SMR may impede airway management and hemorrhage control. 4,7 Moreover, cadaveric and imaging studies suggest that concurrent cervical spine fractures are rare in GSWs to the head and indirect cervical spine injuries do not occur.…”
Section: Introductionmentioning
confidence: 99%
“…In prolonged rescue missions, bag-valve mask ventilation should only serve as a bridge to a protected airway. Immobilisation of the c-spine is not necessarily recommended for all blunt trauma patients (Table 2) [24][25][26] and should not be performed in neurologically intact patients with penetrating trauma [23,[27][28][29][30][31][32][33]. A clinical decision rule, such as NEXUS or the Canadian C-spine Rule, should be used to avoid secondary spinal injury [33][34][35][36].…”
Section: Grade 2cmentioning
confidence: 99%